Mixed-member electoral systems the best of both worlds? - Shugart, Matthew Soberg 1960-; Wattenberg, Martin P. 1956- (Comparative European politics., 2001)
In the view of many electoral reformers, mixed-member systems offer the best of the traditional British single-seat system and PR systems. This book evaluates why the systems have appealed to many countries, and how well expectations have been met.